1993
DOI: 10.1111/j.1399-6576.1993.tb03748.x
|View full text |Cite
|
Sign up to set email alerts
|

Favorable effects of epidural analgesia on hemodynamics, oxygenation and metabolic variables in the immediate post‐anesthetic period

Abstract: Fourteen adult patients undergoing elective major abdominal surgery were divided into two groups. One group received epidural and general anesthesia (epidural group), and 20 ml of 0.125% bupivacaine and 2 mg of morphine were administered epidurally about 30 min before the end of the operation for post-anesthetic analgesia. The other group (control group) received general anesthesia alone with nitrous oxide, oxygen and enflurane. Flow-directed pulmonary arterial and radial arterial catheters were inserted preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The stress response can lead to the increase of platelet aggregation, fibrinogen levels, and the decrease of antithrombin III levels as well. Attenuation of stress response by epidural analgesia can lead to the decrease in production of catecholamines and cortisol, which can ameliorate thrombogenic effects [9,10]. It has also been shown that epidural bupivacaine 0.5% has a direct inhibitory effect on platelet aggregation [11].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The stress response can lead to the increase of platelet aggregation, fibrinogen levels, and the decrease of antithrombin III levels as well. Attenuation of stress response by epidural analgesia can lead to the decrease in production of catecholamines and cortisol, which can ameliorate thrombogenic effects [9,10]. It has also been shown that epidural bupivacaine 0.5% has a direct inhibitory effect on platelet aggregation [11].…”
Section: Discussionmentioning
confidence: 98%
“…Epidural analgesia increases lower limb blood flow and decreases factor VIII activity [4]. The stress response induced by surgery leads to the increase of catecholamines, cortisol, and angiotensin levels (secondary to higher renin activity) [9,10]. The stress response can lead to the increase of platelet aggregation, fibrinogen levels, and the decrease of antithrombin III levels as well.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is greater for a lumbar epidural than a thoracic epidural [ 42 ]. The magnitude of the stress response correlates with postoperative morbidity, and thus, its attenuation should be of benefi t [ 43 ].…”
Section: Neuroendocrinal Effectsmentioning
confidence: 98%
“…In both treatments groups, serum cortisol did not exceed the reference range (0.96 to 6.81 mg/dl) at any evaluated time point. In humans, extradural administration of opioids has been shown to have favorable effects on metabolites and hormonal variables in the immediate postoperative period 28 . Previous studies have reported that dogs receiving ED morphine 29 or ED methadone 3 have lower postoperative serum cortisol levels than those receiving the same analgesic by IV administration.…”
Section: Discussionmentioning
confidence: 99%